FRI0303 PERIPHERAL SYMPTOMS ARE ASSOCIATED WITH LESS SPINAL RADIOGRAPHIC PROGRESSION IN PATIENTS WITH EARLY AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE GERMAN SPONDYLOARTHRITIS INCEPTION COHORT. (2nd June 2020) - Torgutalp, M.; Protopopov, M.; Proft, F.; Sieper, J.; Rios Rodriguez, V.; Haibel, H.; Rudwaleit, M.; Poddubnyy, D.
Abstract : Background: Peripheral symptoms (PS), such as arthritis, enthesitis, and dactylitis, are common in axial spondyloarthritis (axSpA); data showing the association of PS and spinal radiographic progression in axSpA are controversial. Objectives: To analyze the association of PS and spinal radiographic progression in patients with axSpA. Methods: A total of 210 patients with axSpA (115 with radiographic and 95 with non-radiographic axSpA) were selected for analysis. Spinal radiographs were scored by two readers in a random order according to the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). Pelvic radiographs were scored according to the grading system of the modified New York criteria; a sacroiliitis sum score was calculated as a sum of the grades for both sacroiliac joints. Mann-Whitney and Fisher exact tests were performed for group comparisons. A multivariable regression analysis was performed to analyze the influence of PS on radiographic progression. Results: Of the 101 (48.1%) patients with PS, 78 had peripheral arthritis, 48 - enthesitis, 12 - dactylitis. 32 patients had ≤1 PS. Patients with PS were older, less frequently HLA-B27 positive, compared with patients with no PS (73 (73.0%) vs. 93 (85.3%), p=0.028), had higher disease activity (time-averaged ASDAS over 2 years 2.6 ± 0.9 vs. 2.3 ± 0.9; p=0.032), worse physical function (BASFI 3.5 ± 2.3 vs. 2.3 ± 2.2, p<0.001), higher exposure to disease modifying anti-rheumatic drugs (39 (38.6%) vs. 22 (20.2%), p=0.003) and lower baseline radiographic sacroiliitis sum score (3.8 ± 1.9 vs. 4.4 ± 2.1, p=0.026); other baseline characteristics were similar. Patients with PS had lower absolute progression in mSASSS after 2 years of follow-up than those without (0.28 ± 1.39 vs 1.15 ± 2.9, p=0.045); 7.9% of patients with PS had a progression of mSASSS by ≥2 points compared to 20.2% in patients without PS (p=0.011). Radiographic progression of sacroiliitis was similar in both groups. In a multivariable regression analysis, presence of PS was associated with a lower mSASSS progression and lower odds for the mSASSS progression by ≥2 points after 2 years of follow-up: β=-0.98 (95% -1.68 to -0.28) OR=0.33 (95% CI 0.12 to 0.91), respectively – Table 1 . Conclusion: Presence of PS is associated with distinct characteristics of SpA including slower radiographic spinal progression which might be explained partly by the numerically lower mSASSS score at baseline. Acknowledgments: GESPIC has been financially supported by the German Federal Ministry of Education and Research (BMBF). As funding by BMBF was reduced in 2005 and stopped in 2007, financial support has been obtained from Abbott / Abbvie, Amgen, Centocor, Schering-Plough, and Wyeth. Since 2010 GESPIC is supported by Abbvie. Dr. Murat Torgutalp was supported by the Scientific and Technological Research Council of Turkey (TUBITAK). Disclosure of Interests: Murat Torgutalp: None declared, Mikhail Protopopov Consultant of: Novartis, Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Martin Rudwaleit Consultant of: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB